Power Relations in The Iron Claw (2023): A Foucauldian Analysis - Bela Muharamah; M. Afifulloh (MASI Mandiri Edukasi, 2026)
Contemporary cinema has become an important medium for examining power relations within social institutions, particularly the family. The Iron Claw (2023) portrays the tragic story of the Von Erich wrestling dynasty, highlighting how patriarchal authority, masculinity, and bodily discipline shape the lives of family members. Although Foucauldian perspectives have been widely applied in film studies, research specifically examining The Iron Claw through Michel Foucault’s concepts of power remains limited, particularly regarding the interplay of disciplinary power, power/knowledge, biopower, governmentality, and resistance within the family institution. This study aims to analyze how patriarchal power is represented, reproduced, and contested in The Iron Claw using Michel Foucault’s theoretical framework. The study employed a qualitative research design using Foucauldian Discourse Analysis (FDA). The data corpus consisted of the full film, with selected scenes, dialogues, and visual elements, including cinematography, editing, lighting, and sound, purposively selected based on their representation of patriarchal authority, masculinity, bodily discipline, and resistance. The findings suggest that disciplinary power and power/knowledge constitute the dominant mechanisms through which Fritz Von Erich shapes his sons into disciplined subjects who internalize ideals of masculinity, achievement, and family loyalty. The analysis further indicates that bodily commodification represents how the sons’ bodies become resources for preserving family legacy and achieving professional success within the wrestling industry, while governmentality encourages self-discipline and continuous competition. Resistance emerges through Kevin Von Erich’s rejection of inherited patriarchal values and his construction of an alternative understanding of family, masculinity, and personal well-being. Overall, the film suggests that patriarchal power is sustained through discourse, bodily discipline, and self-governance rather than direct domination. This study contributes to Foucauldian film studies by extending the application of Foucault’s theory to sports biopics and enriching scholarly discussions of masculinity and family power relations in contemporary cinema.